Role of adiponectin in sphingosine-1-phosphate induced airway hyperresponsiveness and inflammation. (January 2016) - Nigro, Ersilia; Matteis, Maria; Roviezzo, Fiorentina; Mattera Iacono, Valentina; Scudiero, Olga; Spaziano, Giuseppe; Tartaglione, Gioia; Urbanek, Konrad; Filosa, Rosanna; Daniele, Aurora; D'Agostino, Bruno
Graphical abstract: Abstract: Epidemiological data suggest that obesity represent an important risk factor for asthma, but the link between excess fat and airway hyperresponsiveness (AHR) and inflammation is not fully understood. Recently, a key role in physiopathologic conditions of lungs has been given to adiponectin (Acrp30). Acrp30 is one of the most expressed adipokines produced and secreted by adipose tissue, showing an intriguing relationship with metabolism of sphingolipids. Sphingosine-1-phosphate (S1P) has been proposed as an important inflammatory mediator implicated in the pathogenesis of airway inflammation and asthma. In the present study we analyze the effects of recombinant Acrp30 administration in an experimental model of S1P-induced AHR and inflammation. The results show that S1P is able to reduce endogenous Acrp30 serum levels and that recombinant Acrp30 treatment significantly reduce S1P-induced AHR and inflammation. Moreover, we observed a reduction of Adiponectin receptors (AdipoR1, AdipoR2 and T-cadherin) expression in S1P treated mice. Treatment with recombinant Acrp30 was able to restore Acrp30 serum levels and adiponectin receptors expression. These results could indicate the ability of S1P to modulate the Acrp30 action, by modulating not only the serum levels of the protein, but also its receptors. Taken together, these data suggest that adiponectin could represent a possible biomarker in obesity-associated asthma.